Determination of Transport Properties of Electrolyte With or Without Convection. Issue 4 (1st April 2023) - Delacourt, C.; Rabette, C.
Abstract : There is a variety of electrochemical methods to determine the transport properties of electrolytes. There are also different underlying hypotheses to derive transport equations that are used in these methods. In this work, we examine how the values of the transport properties determined with some of these methods are affected depending on whether convection is neglected in the Onsager-Stefan-Maxwell transport equations. In particular, we show that the values of the diffusion coefficient and the cation transference number that are determined from analyses of experimental data that ignore convection deviate from those that account for it. We exemplify our point using simulations. This work emphasizes that transport properties from the literature can be used in a mathematical model providing the underlying assumptions of the model are compatible with those used for their determination.